2022
DOI: 10.1302/0301-620x.104b2.bjj-2021-1030.r1
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic status and the 30- and 90-day risk of infection after total hip arthroplasty

Abstract: Aims The aim of this study was to examine whether socioeconomic status (SES) is associated with a higher risk of infections following total hip arthroplasty (THA) at 30 and 90 days. Methods We obtained individual-based information on SES markers (cohabitation, education, income, and savings) on 103,901 THA patients from Danish health registries between 1 January 1995 and 31 December 2017. The primary outcome measure was any hospital-treated infection (i.e. all infections). The secondary outcomes were further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Poor glycaemic control, obesity, malnutrition, and smoking are all associated with increased rates of PJI. 36 Edwards et al 37 have highlighted the association between socioeconomic status and the 30- and 90-day increased risk of infection after THA. Surgeons and patients need to be aware of this, and we should have a shared decision-making approach.…”
mentioning
confidence: 99%
“…Poor glycaemic control, obesity, malnutrition, and smoking are all associated with increased rates of PJI. 36 Edwards et al 37 have highlighted the association between socioeconomic status and the 30- and 90-day increased risk of infection after THA. Surgeons and patients need to be aware of this, and we should have a shared decision-making approach.…”
mentioning
confidence: 99%
“…The 90-day period was suggested as the minimum follow-up period to track surgical site infection rates for TKA and THA from linked administrative data. 16,17 Given that there is no gold-standard definition for PJI, we estimated the incidence of 90-day readmission for PJI using three levels of definitions: revision arthroplasty for PJI, as recorded by the AOANJRR; conservative definition of Annual 90-day hospital readmission rate for periprosthetic joint infection (PJI) following primary total hip arthroplasty for osteoarthritis.…”
Section: Methodsmentioning
confidence: 99%
“…The 90-day period was suggested as the minimum follow-up period to track surgical site infection rates for TKA and THA from linked administrative data. 16 , 17 Given that there is no gold-standard definition for PJI, we estimated the incidence of 90-day readmission for PJI using three levels of definitions: revision arthroplasty for PJI, as recorded by the AOANJRR; conservative definition of PJI, as defined by the presence of T84.5 as a primary or secondary diagnosis in the APDC irrespective of the presence of an associated surgical procedure code; and extended definition of PJI, as defined by either T84.5 being recorded as a primary or secondary diagnosis in the APDC, or one or more readmissions in the APDC identified by a combination of diagnosis and procedure code groups determined via expert review and machine learning algorithms, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent investigation of 103,901 patients who underwent THA between 1995 and 2017 and were included in the Danish health registries, Edwards et al concluded that socioeconomic inequality adversely influences the risk of infection after THA 5 . The cumulative incidence of any infection at 90 days was highest in patients who had the lowest amount of savings (1.3% [95% CI, 1.2% to 1.4%]) compared with those who had the highest amount of savings (0.7% [95% CI, 0.6% to 0.8%]), in patients who had the least education (1.1% [95% CI, 1.0% to 1.2%]) compared with those who had the highest education (0.7% [95% CI, 0.5% to 0.8%]), in patients who lived alone (1.5% [95% CI, 1.3% to 1.6%]) compared with those who did not (0.7% [95% CI, 0.7% to 0.8%]), and in patients who had the lowest income (1.6% [95% CI, 1.5% to 1.70%]) compared with those who had the highest income (0.4% [95% CI, 0.3% to 0.5%]).…”
Section: Patient Factors In Relation To Outcomes Socioeconomicsmentioning
confidence: 99%